Cerrahi Hastalarında Amerikan Ağrı Derneği Revize Hasta Sonuçları Anketi’ nin Türkçe Geçerlik – Güvenirliği - Keskin, Aysun (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
The aim of this study is to analyze the valididity-reliability of the Turkish version of Revised American Pain Society Patient Outcome Questionnaire in surgical patients. The sampling of the research has been collected from the patients, who were matching the criteria for the participation and accepted to participate in the research as a volunteer, that had stayed in General Surgery, Orthopedics, Urology, Brain Surgeon, Gynecology clinics at Famagusta State Hospital and Dr. Burhan Nalbantoğlu State Hospital for a period of minimum 24 hours and first 72 hours after the postoperative care. The data of the research has been collected by the researcher between 26th September 2017 and 22nd June 2017. The required institude and board permits have been obtained. Translation and back translation have been done for the language validity of the scale/questionnaire. For the content validity, opinions from 9 experts have been provided. Item Content Index (=0.82) and Scale Content Validity Index (=0.84) have been used for the evaluation of expert opinions. The alpha reliability coefficient of Revised American Pain Society Patient Outcome Questionnaire has been found; for the whole scale/questionnaire as  = 0.91; for sub-dimensions; 0.87 for “Pain Severity and its Effect on Sleep”; 0.92 for “Its Effect on Activity”; 0.95 for “Emotional Effect”; 0.91 for “Side Effects”; 0.50 for “Care Sense”. It has been determined that the reliability coefficient of item-total score correlations of the 18 items in the scale/questionnaire was in a positive direction and statistically very meaningful at advanced level as r: between 0.27 and 0.83 (p<0.001, Table 15). It has been determined that the original scale is in a similar structure with Revised American Pain Society Patient Outcome Questionnaire and has a high validity and reliability. The researcher suggests this scale to be used in the evaluation of pain management quality and patient outcomes in surgical patients and in the planning of appropriate nursing interventions according to the results.

ÖZ: Bu çalışmanın amacı; Cerrahi hastalarında Amerikan Ağrı Derneği Revize Hasta Sonuçları Anketi’nin Türkçe geçerlik–güvenirliği’ ni incelemektir. Araştırmanın örneklemine, Gazimağusa Devlet Hastanesi ve Lefkoşa Dr. Burhan Nalbantoğlu Devlet Hastanesi; Genel Cerrahi, Ortopedi, Üroloji, Beyin Cerrahi, Kadın Doğum kliniklerinde en az 24 saat hastanede kalan, ameliyat sonrası ilk 72 saat içinde olan, araştırmaya dahil edilme kritelerlerine uyan, gönüllü olarak araştırmaya katılmayı kabul eden hastalar alınmıştır. Araştırma verileri 26.02/ 22.06.2017 tarihleri arasında araştırmacı tarafından toplanmıştır. Araştırmanın yapılabilmesi için gerekli kurum ve kurul izinleri alınmıştır. Anket’in dil geçerliliğinde çeviri ve geri çeviri yapılmıştır. İçerik geçerliğinin değerlendirilmesinde 9 uzmandan görüş alınmıştır. Uzman görüşlerinin değerlendirilmesinde Madde İçerik Geçerlik İndeksi (=0.82) ve Ölçek İçerik Geçerlik İndeksi (=0.84) değerlendirilmiştir. Amerikan Ağrı Derneği Revize Hasta Sonuçları Anketi’nin Cronbach alfa güvenirlik katsayısı tüm anket için  = 0.91, alt boyutlarının ise, “Ağrı şiddeti ve Uykuya Etkisi” için; 0.87, “Aktiviteye Etkisi” alt boyutunda; 0.92, “Emosyonel Etki” 0.95, “Yan Etkiler” 0.91, “Bakım Algısı” 0.50 olarak bulunmuştur. Anketin 18 maddesinin madde-toplam puan korelasyonları güvenirlik katsayısı r: 0.27 ile 0.83 arasında, pozitif yönde ve istatistiksel olarak çok ileri düzeyde anlamlı olduğu saptanmıştır (p<0.001, Tablo 15). Amerikan Ağrı Derneği Revize Hasta Sonuçları Anketi’nin orijinal anketle benzer bir yapıda olduğu, geçerlik ve güvenirliğinin yüksek olduğu belirlenmiştir. Anketin, cerrahi hastalarında ağrı yönetimi kalitesinin ve hasta sonuçlarının değerlendirilmesinde ve sonuçlara göre uygun hemşirelik girişimlerinin planlanmasında kullanılması önerilir.
Hemşirelik Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Sağlık Bilimleri Fakültesi, Hemşirelik Bölümü, 2017. Tez Danışmanı: Yard. Doç. Dr. Gülten Sucu Dağ.
Keywords: Hemşirelik; Psikometrik; Kalite Geliştirme; Hasta Sonuçları; Yetişkin; Cerrahi Hastaları; Psychometrics; Quality Improvement; Patient Outcomes; Adult; Surgical Patient